2017
DOI: 10.1177/1054773817705541
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Ulcers Prevalence in the Acute Care Setting: A Systematic Review, 2000-2015

Abstract: Little is known about the prevalence of pressure ulcer (PrU) in acute care settings. The aim of this study is to determine the prevalence rate of PrU in acute care settings and to assess the methodological quality of the reviewed publications. The Cumulative Index to Nursing and Allied Health Literature, British Nursing Index, MEDLINE, and Cochrane Database of Systematic Reviews were searched using the keywords pressure ulcer or decubitus ulcer or bed sore or pressure sore or pressure injury, with prevalence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 40 publications
6
81
2
2
Order By: Relevance
“…Each item can be scored on a scale of 1 to 4 or, in the case of friction/shear, 1 to 3 . A score 18 on the Braden scale score was used to categorise people as being at‐risk …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each item can be scored on a scale of 1 to 4 or, in the case of friction/shear, 1 to 3 . A score 18 on the Braden scale score was used to categorise people as being at‐risk …”
Section: Methodsmentioning
confidence: 99%
“…In the last few decades, many studies on PU prevalence and PU care have been published internationally. Systematic review studies show a wide range of PU prevalence rates among hospitalised patients: 3.1% to 30.0% in the United States (US), 1% to 54% in Europe, 6% in Australia, and 2.7% to 16.8% in Asia . To reduce the prevalence of PUs, various preventive measures and treatments have been implemented in hospitals all over the world …”
Section: Introductionmentioning
confidence: 99%
“…Intensive care units (ICUs) are one of the care settings with a high incidence of PIs, with a prevalence ranging from 14%–33.7% (Coyer et al, ; El‐Marsi, Zein‐El‐Dine, Zein, Doumit, & Badr, ; Mehta, George, Mehta, & Wangmo, ). By contrast, the prevalence of PIs is 7.8%–13.5% in all clinical settings (Mehta et al, ; VanGilder, Lachenbruch, Algrim‐Boyle, & Meyer, ) and from 3%–18.5% in acute care settings (Coyer et al, ; Tubaishat, Papanikolaou, Anthony, & Habiballah, ; Whittington & Briones, ). Similarly, the PI incidence of 13.6%–20.1% in ICUs (Becker et al, ; Manzano et al, ; Nijs et al, ) is almost three times greater than that observed in acute care settings (5.4%–9%) (Jenkins & O'Neal, ; Whittington & Briones, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pressure injury (PI) is defined as “a localized damage to the skin and/or underlying soft tissue usually over a bony prominence.” Currently, the worldwide prevalence of PIs in acute settings is estimated to be between 6% and 15%, while in Singapore, the latest PI prevalence is reported to be 18.1% . This is seen to be a major concern as PIs are often highly regarded to be preventable.…”
Section: Introductionmentioning
confidence: 99%